Salvation as Relational and Structural Restoration in Luke 19:1–10: An Ideological-Critical Reading - Linda Pattirousamal; Adolof Fariman; Musa Edi Sabono; Rineva Lenci Tomasoa (Program Pascasarjana UKIM, 2026)
Poverty represents a persistent form of socio-economic injustice that undermines human dignity, social cohesion, and equitable relationships, including within the context of Maluku. Luke 19:1–10 addresses a comparable reality by exposing ideological structures that sustain economic exploitation, social exclusion, and communal fragmentation. This article examines salvation in the Zacchaeus narrative as relational and structural restoration. Employing a qualitative, literature-based method and Gale A. Yee’s ideological criticism, the study analyzes the political, economic, social, and religious ideologies operating within and behind the text. The findings demonstrate that Jesus’ encounter with Zacchaeus challenges both imperial exploitation and communal exclusion. Zacchaeus’s redistribution of wealth and fourfold restitution signify concrete repentance, restorative justice, and the repair of damaged relationships. Salvation is therefore not limited to individual conversion but includes restored dignity, social reintegration, economic accountability, and resistance to exploitative structures. The study concludes that Luke 19:1–10 offers a transformative theological framework for addressing socio-economic injustice through justice, compassion, accountability, and institutional responsibility.